ANALISIS PENGARUH KOMITMEN ORGANISASI, PENGELOLAAN KEUANGAN DAERAH DAN KINERJA APARATUR TERHADAP GOOD GOVERNANCE (Survey pada Aparatur Pemerintah Daerah Kabupaten Wonogiri) - Lestariningrum, Nisa; Sarwono, Aris Eddy; Kristianto, Djoko (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2021)
The research was conducted on the local government apparatus Wonogiridistrict. This study aims to determine the effect on organizational commitment,regional financial management and apparatus performance on good governance.The type of data used in this research is quantitative data, the data source used isprimary data. The population in this study were all local government officials inWonogiri district. The number of samples in this study were 102 respondents. Thesampling technique used purposive sampling. The data collection method usedwas a questionnaire. The data analysis teqnique used is descriptive statistics,validity test, reliability test, classicalassumption test and multiple linierregression. The results show that the variable of organizational commitment,regional financial management and apparatus performance have a significantpositive effect on good governance.